Nursing resources and innovations for hospital discharge: an integrative review - Cieto, Bianca Bolzan (2014)
This study aimed to identify nursing resources and innovations applied to patient discharge. It is an integrative literature review in which PubMed, Cochrane, LILACS and SciELO databases were used. Sample consisted of 12 articles. The use of a checklist, an ultra-short hospitalization programme and a liaison nurse were identified as nursing innovations. The resources were as follows: multidisciplinary teamwork, integration between primary care, specialized care, social services and hospital discharge, telephone follow-up after discharge, whiteboard, electronic health record, written educational material, printed care plan, discharge protocols, case management, audio tapes, booklet with phones and web sites of community services, continuing education of health professionals, discharge coordinator, nurse facilitated discharge and nurse educator. In conclusion, resources and innovations may help managers and health professionals in improving their discharge procedures